2021
DOI: 10.3390/cancers14010150
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax for Children and Adolescents with Acute Lymphoblastic Leukemia and Lymphoblastic Lymphoma

Abstract: Venetoclax is approved for adult patients with chronic lymphocytic leukemia and acute myeloid leukemia. Expanding its use to the pediatric population is currently under investigation, but more robust data are needed. We retrospectively analyzed the safety and efficacy of venetoclax in children/AYA with ALL/LBL. We identified 18 patients (T-cell ALL, n = 7; T-cell LBL, n = 6; B-cell ALL, n = 5) aged 6–22 years. No new venetoclax safety signals were identified; the most common toxicity was myelosuppression. No d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 36 publications
(44 reference statements)
1
31
0
Order By: Relevance
“…A phase I study on 29 pediatric patients with r/r AML and ALL treated with venetoclax plus chemotherapy reported no significant increase in infection rates, even though febrile neutropenia was documented in 45% of patients [ 216 ]. A retrospective study of 18 pediatric patients who received venetoclax for ALL and T-lymphoblastic lymphoma observed grade ≥3 infectious complications in half of the patients: 27.8% were found with sepsis, 27.8% with febrile neutropenia, 5.6% with pneumonia, 5.6% with mucosal infection, and 55.6% with neutropenia [ 217 ]. The same research group conducted a study involving 36 pediatric patients with r/r AML under venetoclax combined with chemotherapy and calculated a rate of grade ≥3 febrile neutropenia at 58.3% [ 218 ].…”
Section: Other Targeted Therapies With Off-label Usementioning
confidence: 99%
“…A phase I study on 29 pediatric patients with r/r AML and ALL treated with venetoclax plus chemotherapy reported no significant increase in infection rates, even though febrile neutropenia was documented in 45% of patients [ 216 ]. A retrospective study of 18 pediatric patients who received venetoclax for ALL and T-lymphoblastic lymphoma observed grade ≥3 infectious complications in half of the patients: 27.8% were found with sepsis, 27.8% with febrile neutropenia, 5.6% with pneumonia, 5.6% with mucosal infection, and 55.6% with neutropenia [ 217 ]. The same research group conducted a study involving 36 pediatric patients with r/r AML under venetoclax combined with chemotherapy and calculated a rate of grade ≥3 febrile neutropenia at 58.3% [ 218 ].…”
Section: Other Targeted Therapies With Off-label Usementioning
confidence: 99%
“…To date, published reports have concluded venetoclax is well-tolerated in combination with a variety of cytotoxic agents in pediatric/AYA patients with hematologic malignancies. [11][12][13][14] Our experience calls attention to the severity and range of atypical infections patients experienced during treatment with venetoclax. Five patients (38%) experienced at least one opportunistic infection, including bacteremia caused by multiple uncommon organisms, invasive pulmonary fungal disease, CMV viremia, and Grade 4 encephalitis with bacterial brain abscesses in one case.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another phase I dose escalation study demonstrated venetoclax with chemotherapy and low-dose navitoclax, a BCL-X L /BCL-2 inhibitor, is a safe and promising combination in pediatric and adult patients with advanced ALL and lymphoblastic lymphoma. 12 Aside from these early-phase trials, the published literature to date concerning venetoclax in pediatric/AYA patients with hematologic malignancies consists of a few single-institution reports that support the safety and efficacy of venetoclax in combination with cytotoxic chemotherapy in pediatric patients with ALL 13 and AML 14 and in combination therapy with azacitidine in pediatric patients with MDS or AML unfit for standard chemotherapy. 15 While these reports are encouraging, more robust data are needed to guide clinicians in the safe and efficacious use of venetoclax combination therapy across a range of pediatric hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to B-ALL, the Bcl-2 and Bcl-x L dependence of cell lines and primary cells has prompted clinical trials of BCL2 antagonists as single agents or combination therapies [ 70 , 71 ]. A retrospective study confirmed the safety and efficacy of venetoclax when compared with conventional treatments of ALL in pediatric patients [ 72 ]. In a phase I study (NCT03181126), a combination of venetoclax with low-dose navitoclax and chemotherapy was well tolerated in both pediatric and adult patients with R/R B/T-ALL [ 73 ].…”
Section: Current Treatments and Clinical Trials Of B Cell Malignancie...mentioning
confidence: 94%